Case of Rhabdomyolysis in a Patient Undergoing Hemodialysis: A Possible Association with Tramadol HCl - Trabulus, Sinan; Seyahi, Nurhan; Özbalak, Murat; Apaydın, Tuğçe; Kaya, Eda; Özkaya, Hande Mefkure; Açbay, Özer (Cerrahpaşa Medical Journal, 2019)
Tramadol hydrochloride (HCl) is a synthetic analgesic agent, which is generally safe at a low dose. Its adverse effects are reported in cases of intoxication. Here we present a 59-year-old male patient with multiple relapsing parathyroid carcinoma-related refractory hypercalcemia and generalized pain. Being prescribed tramadol HCl, he consumed an increased dosage following increased pain, resulting in rhabdomyolysis, which improved after cessation of the drug. Nevertheless, the patient died owing to pulmonary embolism. Rhabdomyolysis owing to tramadol HCl consumption is very rarely reported. Rhabdomyolysis should be considered in patients consuming tramadol HCl and having generalized muscle weakness. Cite this article as: Trabulus S, Özbalak M, Kaya E, Apaydın T, Özkaya HM, Açbay Ö, et al. Case of rhabdomyolysis in a patient undergoing hemodialysis: a possible association with tramadol HCl. Cerrahpasa Med J 2019; 43(1): 34-36.